Criminal Responsibility of Defendant in the Crime of Selling Housing Units that Have Not Completed the Status of Land Rights: (Study of Supreme Court Decision Number: 635 K/Pid.Sus/2019) - Adhi Wibowo (Ekasakti Journal of Law and Justice, 2023)
The crime of selling a housing unit that has not completed its land title status is regulated in Article 154 of Law Number 1 Year 2011 on Housing and Settlement Areas. The act of selling housing without clear land rights status is very detrimental to the community, especially buyers as consumers who need a house to live in, as happened in Padang City. The criminal responsibility of the defendant who violated this provision was punished with imprisonment for 1 (one) year based on the consideration of the cassation judge in the Supreme Court Decision Number: 635 K/Pid.Sus/2019